Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Unknown speaker. Under him: Alexander Berkman and Emma Goldman. Third from the left Maksimov. Left: Gujewski
Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Unknown speaker. Under him: Alexander Berkman and Emma Goldman. Third from the left Maksimov. Left: Gujewski.